Genealogy of the Interpretation of the Holy Qur'an by Mahmud Yunus (A Study of the Context of Modernization of Qur'anic Interpretation in Indonesia): دراسة سياقية في تحديث التفسير القرآني في إندونيسيا - Siti Zulaikha; Bahrudin Zamawi; Rafi Ibnu Mirwan Surianto (ZAD Al-Mufassirin, 2025)
This study explores the impact of modernization in Indonesia on the genealogy of Qur’anic exegesis (tafsīr al-Qur’ān al-Karīm), understood as the historical transmission, intellectual lineage, and transformation of interpretive methods and orientations across generations of Indonesian Muslim scholars. Employing a qualitative, library-based approach, this research analyzes major Indonesian Qur’anic commentaries (kutub al-tafsīr) to identify shifts in interpretive methodology and thematic emphasis. The findings indicate that the modernization of Qur’anic exegesis in Indonesia is characterized by three main features: (1) the reinterpretation of Qur’anic verses related to science (al-‘ilm) and rational inquiry (al-‘aql), (2) a strong emphasis on social and societal issues (al-masā’il al-ijtimā‘iyyah), and (3) the systematic use of the Indonesian language as a medium of interpretation. These elements collectively demonstrate a shift toward a more contextual, socially responsive, and accessible model of Qur’anic interpretation. This study provides a foundation for the development of contemporary Indonesian exegesis by outlining a locally grounded methodological framework that integrates modernist hermeneutics with classical Islamic scholarship, offering a model of interpretation that remains rooted in tradition while responding effectively to present-day religious and social challenges.